Language Power in the Classroom Viewed from Nietzsche and Heidegger - Moh. Yamin; Fabiola Dharmawanti Kurnia; Ali Mustofa (OKARA: Jurnal Bahasa dan Sastra, 2020)
Language should be viewed as the space to build the interaction. The classroom practice in which the teacher and students interact in a teaching-learning activity should be empowered through language. To produce a language aura that can be paid attention by the participants, it is important to put language as the power in the positive side in which every participant respect the language as the power to tie each other. This study aims to explore Nietzsche's and Heidegger's views on the use of language and language power in the classroom and to compare both of their views in the classroom. The expected study is that it has the significance of using the language as the center of communication and teaching-learning. The descriptive qualitative method is applied. The data are taken from four research articles on Nietzsche's and Heidegger’s views dealing with language power in the classroom. Findings and results from each research article are the data for this study. Every finding and result of the research article becomes the data source to discuss. The findings show that the capability in using language can be the space of power so that it drives the class to become effective and there is an interactive dialogue between the teacher and students.